Evaluating the use of the interferon‐γ response to Mycobacterium tuberculosis‐specific antigens in patients with psoriasis prior to antitumour necrosis factor‐α therapy: a prospective head‐to‐head cross‐sectional study. (25th April 2013) - Martyn‐Simmons, C.L.; Mee, J.B.; Kirkham, B.W.; Groves, R.W.; Milburn, H.J.
Summary Background Targeted biological therapies have transformed the treatment of chronic inflammatory disease. However, reactivation of latent tuberculosis infection (LTBI) is a significant risk with the use of antitumour necrosis factor (anti‐TNF)‐α therapy and screening is mandatory prior to treatment. The tuberculin skin test (TST) may be difficult to interpret in patients with inflammatory disease or receiving immunosuppressive therapies. Objectives The aim of this study was to evaluate and compare the QuantiFERON®‐TB Gold In‐Tube (QFR) and T‐SPOT.TB (TSTB) interferon‐γ‐release assays (IGRA) against the TST in a cohort of patients commencing anti‐TNF‐α therapies for chronic inflammatory disease. Methods A prospective cross‐sectional study was undertaken at a London tertiary referral centre. Demographic data collected included TB risk factors. TST, QFR and TSTB were performed in all patients. Results Seventy patients with chronic plaque psoriasis were included in the study. Agreement between QFR and TSTB, excluding indeterminate results, was 89% (κ = 0·567), between QFR and TST 85% (κ = 0·313) and 81% (κ = 0·244) between TSTB and TST. There was no significant association with concomitant immunosuppression and either TST or IGRA results. Seven patients received chemoprophylaxis for LTBI diagnosed after clinical risk assessment together with positive TST and/or IGRA. Three patients had positive results in all three tests. Conclusions While there was moderate overall agreement between QFR and TSTB and fair correlation between TST, QFR and TSTB, there were a number of discordant results, suggesting that a three‐pronged approach using TST, QFR and TSTB may be of additional benefit.